2014
DOI: 10.1063/1.4903075
|View full text |Cite
|
Sign up to set email alerts
|

Local formation of nitrogen-vacancy centers in diamond by swift heavy ions

Abstract: We exposed nitrogen-implanted diamonds to beams of swift heavy ions (~1 GeV, ~4 MeV/u) and find that these irradiations lead directly to the formation of nitrogen vacancy (NV) centers, without thermal annealing. We compare the photoluminescence intensities of swift heavy ion activated NVcenters to those formed by irradiation with low-energy electrons and by thermal annealing. NVyields from irradiations with swift heavy ions are 0.1 of yields from low energy electrons and 0.02 of yields from thermal annealing. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Since T 2 and T 2 * times are ultimately limited by nitrogen concentration, it is important to maximize the yield of NV − centers. A popular way of increasing NV − yield is irradiation of diamond with electrons and subsequent annealing [23,24]. The first step creates additional vacancies necessary for the formation of NV − centers, but also generates a lot of interstitial carbon and nitrogen atoms, which could be source of strain.…”
Section: Coherence Properties Of Diamond Platesmentioning
confidence: 99%
“…Since T 2 and T 2 * times are ultimately limited by nitrogen concentration, it is important to maximize the yield of NV − centers. A popular way of increasing NV − yield is irradiation of diamond with electrons and subsequent annealing [23,24]. The first step creates additional vacancies necessary for the formation of NV − centers, but also generates a lot of interstitial carbon and nitrogen atoms, which could be source of strain.…”
Section: Coherence Properties Of Diamond Platesmentioning
confidence: 99%
“…NVC's are atomic-scale defects which are formed either naturally or by implantation, using high-energy nitrogen ion beam [26], annealing [27,28], and nitrogen doping [29]. The NVC spin states are split under the influence of an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations concluded that irradiation of diamond is more likely to directly create NV defects, and not isolated vacancies. Direct NV creation has been shown without thermal annealing by irradiation of diamond that has been implanted with nitrogen ions with low-energy electrons (2−30 keV) [109] and beams of swift heavy ions (∼1 GeV, ∼4 MeV/u) [110]. However, this model of direct NV creation is contradicted by other works.…”
Section: Synthetic Creation Of Defect Centersmentioning
confidence: 98%
“…In the last few years, research has been done to control the orientation of NV centers during CVD growth and thus increase the device yield. Initial studies showed that diamond grown with homoepitaxial CVD growth on [110] [143] and [100] [144] oriented substrates mainly supports two NV orientations when the growth parameters are controlled precisely. Further work showed that for NV centers created during CVD of diamond on [111] surfaces, microwave plasma-assisted CVD yields 94% of NV centers along a single crystallographic direction [145].…”
Section: G Dipole Orientation Of Defectsmentioning
confidence: 99%